We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
63
1
avatar

 

x1+x2+x3=0

x2=0

solve using back substitution

 Feb 21, 2019
 #1
avatar+100578 
+3

All we know....after substitution....is that

 

x1 + x3 = 0       so

 

x1 =   - x3

 

That's as much as we can do....

 

 

cool cool cool

 Feb 21, 2019

16 Online Users

avatar